Fabrication and characterization of electrospun poly(3-aminobenzylamine)/ functionalized multi-walled carbon nanotubes composite film for electrochemical glucose biosensor - Saengrawee Sriwichai; Sukon Phanichphant (eXPRESS Polymer Letters)
A glucose sensor has been developed for daily diagnosis due to high level of glucose can cause diabetes. This study purposes of fabricating an electrospun fiber film of poly(3-aminobenzylamine) (PABA)/functionalized multi-walled carbon nanotubes (f-CNTs) composite for use as electrochemical glucose biosensor. The electrospun PABA/f-CNTs composite film was fabricated on a screen-printed electrode and characterized by attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), and field emission–scanning electron microscopy (FE-SEM). The presence of f-CNTs in the composite could enhance the electrochemical activities of the PABA, which was confirmed by cyclic voltammetry (CV), amperometry, and electrochemical impedance spectroscopy (EIS). The electrochemical glucose biosensor based on the electrospun PABA/f-CNTs composite film showed a sensitivity of 0.40 μA·mm–2·mM–1 with LOD of 0.067 mM in the linear range of 0.56–2.8 mM, high selectivity under the common interferences (i.e., uric acid, ascorbic acid, and dopamine) and good stability up to 1 week with the current response retained about 80%.